Medical students’ publications produced in the Epidemiology course of the Faculty of Medicine, San Marcos University during the period 2003-2009 - Alarcón-Villaverde, Jorge (2010)
Background: The epidemiology course is taught in the 5th year of undergraduate Academic Professional School of Human Medicine, Faculty of Medicine of the San Marcos University. One of the outcomes at the end of this course is research that usually will not be published. Objectives: To determine the percentage of research produced during the course of epidemiology and published in biomedical journals during the period 2003-2009. Design: Bibliometric study. Setting: Epidemiology Section, Institute of Tropical Medicine, Universidad Nacional mayor de San Marcos, Lima, Peru. Bibliographic material: Research work published. Methods: Papers elaborated in the epidemiology course and published in biomedical journals during the period 2003-2009. Main outcome measures: Number of research papers produced and published in biomedical journals. Results: From 110 research works 13 (11.8%) were published in biomedical journals. Authors average number per paper was 7 students; 8 papers considered the tutor as an author. Conclusions: The production of student publications is low. Peruvian physicians’ lack of interest in publishing is observed since undergraduate. There are factors associated with the student, study plans and biomedical journals that could explain this phenomenon.